Insights on carbapenem-resistant Acinetobacter baumannii: phenotypic characterization of relevant isolates - Donadu, Matthew Gavino; Zanetti, Stefania; Nagy, Ádám László; Barrak, Ibrahim; Gajdács, Márió (Acta Biologica Szegediensis, 2021)
Acinetobacter baumannii (A. baumannii) is an important nosocomial pathogen, which may be a causative agent in a wide-range of human pathologies. Carbapenems are usually considered the last safe and eﬀective choice of drugs for the treatment of Gram-negative infections. The emergence of carbapenem-resistant A. baumannii (CRAB) is a critical public health issue as they leave clinicians with limited therapeutic options. In this study, phenotypic methods were used to characterize sixty-two (n = 62) A. baumannii isolates, which were included based on their suspected non-susceptibility to meropenem. Minimum inhibitory concentrations (MICs) of meropenem, levofloxacin, gentamicin, sulfamethoxazole/trimethoprim, tigecycline were determined using E-tests, while colistin MICs were determined using broth microdilution. The isolates were subjected to the modiﬁed Hodge test (MHT), the modiﬁed carbapenem-inactivation method (mCIM) and the imipenem/EDTA combined disk test (CDT). Eﬄux pump overexpression was studied using agar plates containing phenylalanine-arginine β-naphthylamide (PAβN). Assessment of bioﬁlm-formation was carried out using the crystal violet tube-adherence method. 64.5% of the strains showed meropenem MICs in the resistant range (>8 mg/L), resistance rates were similarly high to the other tested antibiotics. The MHT and mCIM assay were positive in 79.0% and 67.7% of cases, respectively; the presence of an MBL was suggested for 29.0% of isolates. Eﬄux-pump overexpression was seen in 12.9% of isolates. 54.8% of the isolates were characterized as strong bioﬁlm-producers. Microbiology laboratories have an important role in diﬀerentiating the distinct mechanisms by which these pathogens develop the CRAB phenotype, as plasmid-borne carbapenemases are signiﬁcant from the standpoint of public health microbiology.